Igreja: desafios inusitados. Pedofilia: primeiras reações e interpelações - Moser, Antônio (Revista eclesiástica brasileira, 2002)
A wave of denouncements of pedophilia in the clergy, chiefly in the Anglo-Saxon context, put the Catholic Church in a very difficult situation. Facing this, it be best to act with discernment, accepting the facts, but also trying to reproportion them. Pedophilia is not, evidently, a problem which only exists within the Church, nor is it an isolated problem: it is linked to a society which is sexually and socially disjointed. The incitement of the genitality seems to be at the root of this and other sexual deviations. Standing before this world of shadows, a revision in the formative structures of the clergy and the religious life is urgent, but above all a large investment in terms of education for love.